Effect of lactic acid sprays on shelf life and microbiological safety of beef subprimals - Prasai, R.K.; Mease, L.E.; Vogt, L.R.; Kropf, Donald H.; Fung, Daniel Y. C.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Beef loins were sprayed with 1.5% lactic acid either before or after vacuum storage, both before and after vacuum storage, and before vacuum packaging followed by a water spray after storage. We stored treated loins at either 30 ̊F or 36 ̊F for up to 126 days in vacuum packages. Nonsprayed or nonstored loins served as controls. Total aerobic plate counts (APCs) and tests for presence/absence of two important foodborne pathogens, Salmonella spp. and Listeria monocytogenes, were conducted during storage. Acid spraying prior to vacuum packaging was more effective in reducing bacterial contamination than spraying after storage. However, counts were reduced (P<.05) for only 28 days of storage. Most loins stored at 30 ̊F had lower APCs than those stored at 36 ̊F. Salmonella was not detected in any samples. Twenty-eight percent of nonacid treated and 4 percent of acid-treated loins were positive for Listeria spp. with L. monocytogenes found from one nonacid-treated loin. No change in visual color was observed in acid-treated loins. Appropriate timing of acid s praying in combination with lower storage temperature can improve the keeping quality and microbial safety of meat.
Keywords: Beef; Lactic acid; Bacteria; Safety